The National Solid Waste Policy and the importance of public policies for environmental quality - Rigoldi, Kelly Cristina; Lima, Valéria (Electronic Journal "Fórum Ambiental da Alta Paulista", 2023)
The densification of urban settlements and the advancement of science and technology, from the capitalism perspective, has intensified the society relationship with nature, highlighting environmental problems. Several environmental impacts are observed, such as the issue of solid waste, which results in both environmental and social damage. Public policies aim to solve problems that affect the environmental and life quality of population. It was in this sense that the National Solid Waste Policy (PNRS) was drawn up in 2010. This article aims to understand and evaluate how the National Solid Waste Policy (PNRS) aligns with discussions on environmental issues, public policies and the importance of an analysis of the totality for resolving complex problems. The analyzes carried out showed that the National Solid Waste Policy did not consider the diversity that exist in the national territory, such as the economic potential of the municipalities, thus making the effectiveness of the plan impossible, resulting in numerous reevaluations and extension of deadlines for the plans and targets throughout its validity.